The cycloid and skeletonization methods for morphometric analysis of fetal brain vessels - Stępień, Tomasz; Obara, Bogusław (Folia Neuropathologica, 2008)
In our study, we examined 54 images from 9 fetal brains from the 11th to 22nd gestation week (GW). We measured the length density (LD) of vessels (µm/µm2) in the cortical grey matter (CGM) and in the cortical white matter (CWM). The aim of this work was to find a method which could be applied to measure the length density of vessels on two-dimensional (2D) sections. The first method (cycloid method) was based on cycloid function based on Stereo Investigator Software (MicroBrightField). The length in 2D could be estimated on the basis of a number of intersections between a line-probe and the linear objects of interest. In the study, we used a line-probe with systematically spaced sine-weighted curves (cycloids) of known length. In this case, the cycloids were 53.1 µm long. The counting grid was constructed from sine-weighted lines (cycloids), which were used for estimation of the length density of vessels. The second method (skeletonization) was based on the mathematical functions of morphology and colour system transformation. The “binary airway tree” formed by the image segmentation step was skeletonized to identify two- or three-dimensional centrelines of individual branches, and to determine the branch point locations. The idea was to utilize a skeletonization algorithm which was based on properties of the average outward flux of the gradient vector field of a Euclidean distance function from the boundary of the structure. Both of these methods (cycloid and skeletonization) could be applied in measuring the length density of vessels on two-dimensional (2D) sections. These morphometric methods allowed us to measure the length density in fetal development of vessels in the cortical grey matter and the cortical white matter. The cycloid method could be applied to measure an approximate length density of vessels. However, skeletonization should be applied to measure more precisely length density of vessels in the cortical grey matter and the cortical white matter.